Pengaruh Media Pembelajaran Audio Visual Terhadap Minat Belajar Siswa Sekolah Dasar - Adiyana Adam (LPPM Universitas Terbuka, 2023)
One of the efforts of educators to increase students' interest in learning is to use various learning media, one of the media used is audio-visual. The problem in this study is how the influence of audio-visual learning media on the learning interest of elementary school students. The purpose of this study was to determine the use of audio-visual learning media on elementary school students' learning interests. The method used in this research is descriptive quantitative with data analysis using Excel. The sample in this study were 12 elementary school students who were randomly selected. The results showed that the students were very happy, interested and very interested in using audio-visual learning media in the teaching and learning process. With very high student interest and interest, this in turn influences student learning outcomes. Students can understand learning material more quickly. The implications of this research are improving the quality of student learning, developing learning models and increasing student understanding.